PERLINDUNGAN DAN AKIBAT HUKUM TERHADAP KEBENDAAN MILIK AHLI WARIS DARI SEORANG DEBITUR YANG TELAH MENINGGAL DUNIA - ABDUL ROKHIM (The Juris, 2021)
In practice, financing in the current era is rife, not only legal entities that can become debtors in financing, private legal subjects can also act legally in terms of financing. then the right step to resolve it is through the instrument of bankruptcy law, containing a rule that can regulate the relationship of the parties and also regarding rights and obligations. The results show that the responsibility of the heirs to the debtor who dies and is declared bankrupt the heirs can choose one of 3 (three) attitudes, namely: accept as a whole, be inclusive of the debtor of the heir, accept with conditions, the inheritance is received in detail, while the debt the heir will be paid based on the property received by the heir, and refuse the heir does not want to know about the management of the settlement of the inheritance. Protection of property belonging to an heir of a debtor who has died and is declared bankrupt, namely the bankrupt debtor who still has the right to control and manage certain goods as stipulated in Article 22 in conjunction with Article 21 of the Bankruptcy Law and Suspension of Debt Payment Obligations, which excludes or separates personal assets of the debtor that are not related to the assets that have been bankrupt.